Public Key Cryptography PKC 2010 13th International Conference on Practice and Theory in Public Key Cryptography, Paris, France, May 26-28, 2010. Proceedings - Nguyen, Phong Q.; Pointcheval, David. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 13th International Conference on Practice and Theory in Public Key Cryptography, PKC 2010, held in Paris, France, in May 2010. The 29 revised full papers presented were carefully reviewed and selected from 145 submissions. The papers are organized in topical sections on encryption; cryptanalysis; protocols; network coding; tools; elliptic curves; lossy trapdoor functions; discrete logarithm; and signatures.